GPER Signaling in Spermatogenesis and Testicular Tumors - Chimento, Adele; Sirianni, Rosa; Casaburi, Ivan; Pezzi, Vincenzo (Frontiers in Endocrinology, 2014)
ABSTRACT Estrogens play important roles in the regulation of testis development and spermatogenesis. Moreover, several evidences suggest that estrogen signaling can be involved in testicular tumorigenesis. The physiological effects of estrogen are mediated by the classical nuclear estrogen receptors (ERs) ESR1 and ESR2, which regulate both genomic and rapid signaling events.. In the last years, a member of the 7-transmembrane G protein-coupled receptor family, GPR30 (GPER), has been identified to promote estrogen action in target cells including testicular cells. Ours and other studies reported that GPER is expressed in normal germ cells (spermatogonia, spermatocytes, spermatids), somatic cells (Sertoli and Leydig cells) and it is also involved in mediating the estrogen action during spermatogenesis and testis development. In addition, GPER seems to be involved in modulating estrogen-dependent testicular cancer cell growth. However, in this context, the effects of GPER stimulation on cell survival and proliferation appear to be cell type specific. This review summarizes the current knowledge concerning the functions regulated by estrogens and mediated by GPER in normal and tumor testicular cells.